BACTERIOLOGICAL AND HISTOPATHOLOGICAL STUDIES ON PULMONARY ABSCESSES IN CAMELS (Camelus dromedarius) SLAUGHTERED AT NYALA SLAUGHTERHOUSE, SOUTH DARFOUR STATE, SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
A total of 712 camels were presented for slaughter at Nyala slaughterhouse during March 2009 to May 2010. Ninety five camels revealed presence of abscess lesions in their lungs with a prevalence rate of 13.3%. Ninety five specimens were collected from the lung abscesses and processed for bacterial isolation and histopathological examination. Bacterial growth was observed in 70 (73.7%)samples, 60 (85.7%) of them showed pure growth, while 10 (14.3%) showed mixed growth on cultured media. Total of 82 bacterial isolates were Staphylococcus spp. 27(32.9%), Streptococcus spp. 18(21.9%), Corynebacterium spp. 10(12.2%), Pseudomonas spp. 5(6.0%), Arcanobacterium pyogenes 4(4.9%), Proteus spp. 4(4.9%), Micrococcus spp. 3(3.8%), Pasteurella multocida 3(3.8%), Enterococcus spp. 2(2.4%), Enterobacter aerogenes 2(2.4%), Klebsiella pneumoniaesubsp.pneumoniae 2(2.4%), Bacillus cereus 1(1.2%), Rhodococcus equi 1(1.2%). In 10 samples, more than one species were isolated from a single abscess. For example, C. renale was isolated with S. aureus, Pseud.aeruginosa with C. pseudotuberculosis, and Enter. aerogenes with A. pyogenes. The histopathological sections of the lung abscesses revealed central necrotic areas, acute interstitial pneumonia, chronic interstitial pneumonia, bronchopneumonia, oedema and emphysema. Most the lungs abscesses contained S. aureus, Strept. pyogenes, C. pseudotuberculosis, A. pyogenes and Pseud. aeruginosa. In addition, K. pneumoniae subsp.pneumoniae and S. aureuswere isolated from acute interstitial pneumonia and oedema while Strept. pyogenes, Past. multocida and Pseud. aeruginosa were isolated from chronic interstitial pneumonia and bronchopneumonia. This study showed a high incidence of pulmonary abscesses and we recommend working to avoid this infection in order to ensure access to safe meat for human consumption.
Keywords: Bacterial; Histopathological; Pulmonary; abscesses; Dromedary; Camels; South DarfurState